Association of Surgical Overlap during Wound Closure with Patient Outcomes among Neurological Surgery Patients at a Large Academic Medical Center. Issue 5 (6th May 2019) - Glauser, Gregory; Agarwal, Prateek; Ramayya, Ashwin G; Chen, H Isaac; Lee, John Y K; Schuster, James M; Osiemo, Benjamin; Goodrich, Stephen; Smith, Lachlan J; McClintock, Scott D; Malhotra, Neil R
Abstract: BACKGROUND: Several studies have explored the effect of overlapping surgery on patient outcomes, but impact of surgical overlap during wound closure has not been studied. OBJECTIVE: To examine the association of overlap during wound closure and suture time overlap (STO) with patient outcomes in a heterogeneous neurosurgical population. METHODS: Over 4 yr (7/2013-7/2017), 1 7689 neurosurgical procedures were retrospectively reviewed at a single, multihospital academic medical center. STO was defined as all surgeries for which an overlapping surgery occurred, exclusively, during wound closure of the index case being studied. We excluded nonelective cases and overlapping surgeries that involved overlap during surgical portions of the case other than wound closure. Tests of independence and Wilcoxon tests were used for statistical analysis. RESULTS: Patients with STO had a shortened length of hospital stay (100.6 vs 135.1 h; P  < .0001), reduced deaths in follow-up (1.59% vs 5.45%; P  = .0004), and lower 30- to 90-d readmission rates (3.64% vs 7.47%; P  = .0026). Patients with STO had no increase in revision surgery. Patients with STO had longer wound closure times (26.5 vs 23.9 min; P  < .0001) but shorter total surgical times (nonclosure surgical time 101.8 vs 133.3 min; P  < .0001; and total surgical time 128.3 vs 157.1 min; P  < .0001). CONCLUSION: Surgical overlap during wound closure (STO) is associated with improved or at least noninferior patient outcomes, as it pertains to readmissions and wound revisions.